The mediating role of flow experience in the relationship between Tiktok platform quality and tourists' behavioural intention in Chongqing , China - Congying, Liu (2025)
The tourism industry plays a crucial role in the economic growth of a country, like China. This research specifically focused on the factors influencing the quality of TikTok as a short video platform, and how it drives flow experience and tourists’ behavioural intention in Chongqing, China. This research is different from other studies as it examines the mediating role of flow experience in the tourism sector in China. The present study tested the mediating role of flow experience in the relationship between system quality, information quality, and service quality, and tourists’ behavioural intention. Furthermore, this study employed the Stimulus- Organism-Response (S-O-R) model as the underlying model and the cognitive appraisal theory (CAT) as the underpinning theory. A cross-sectional design was employed in this research, and data were collected using the “questionnaire star” platform. The questionnaire was distributed to 492 TikTok users in China. However, only 377 surveys were deemed valid for further analysis. This research utilized PLSSEM to establish the validity and reliability of the measurement model, and test each hypothesis. The outcomes of this research are that system quality, information quality, and service quality, have a significant influence on tourists’ behavioural intention. The results also reveal the mediating role of flow experience in the relationship between system quality, information quality, and service quality, and tourists’ behavioural intention. The outcome of this present study provides new knowledge and important insights for government agencies, tourism industry researchers, and policymakers. Additionally, the research contributes to theory by extending the S-OR model as well as the CAT, and integrating distinct literature streams about system quality, information quality, service quality, flow experience, and tourists’ behavioural intention. Lastly, the research highlights the limitations and implications of the study, as well as suggestions for future research